The impact of oxidative stress on Par2, Ptgs2 genes expression in rat duodenal epithelial cells under conditions of prolonged gastric hypochlorhydria and with administration of multiprobiotic - Alevtina Dranitsina, Kateryna Dvorshchenko, Dmytro Grebinyk, Lyudmila Ostapchenko (Journal of Applied Pharmaceutical Science, 2016)
Development of dysbiosis is a key consequence of long hypoacidity, in which there is colonization of the gastrointestinal tract by pathogenic microflora that forms source of sustainable endogenous infection and leads to inflammation. The prevalence of free-radical processes of antioxidant defense system is an important pathogenetic link in the origin and development of various disorders. Because reactive oxygen species are important for transcription of Ptgs2 gene, the relationship between oxidative stress, antioxidant element and PAR2-mediated signaling pathways may take place under conditions of dysbiotic changes due to hypochlorhydria. To evaluate the intensity of free radical processes and their impact on Par2, Ptgs2 genes expression in rat duodenal epithelial cells under conditions of prolonged gastric hypochlorhydria and with administration of multi-probiotic. Four experimental groups were created with 8 rats in each. One group was a control, while others were injected with acid suppressant omeprazole or multi-strain probiotic preparation or with both compounds simultaneously for 28 days. Protein oxidative modification products, free SH-groups, metallothioneins content were measured in villus and crypt epithelial cells with standard biochemical assays. Level of Par2, Ptgs2 genes mRNA was determined with semi-quantitative RT-PCR. Prolonged inhibition of acid secretion in stomach was accompanied by significant elevation of free radical processes (intensification of protein oxidative modification, free SH-groups pool reduction, changes of metallothioneins concentration) and elevation of Par2 and Ptgs2 genes expression levels in rat duodenal epithelial cells. Reduction of free radical processes intensity; restoration of redox balance and the normalization of Par2, Ptgs2 gene expression pattern in the duodenum upon the simultaneous administration of the multi-probiotic Symbiter were observed. Par2 over-expression leads to activation Ptgs2 on the background of free radical processes over the antioxidant defense system in the development of inflammation in the duodenum through dysbiotic changes in the conditions of prolonged hypochlorhydria.
Keywords: Hypochlorhydria,proton pump inhibitor, dysbiosis, multi-probiotic, gene expression.